An equation is shown below:
(4x - 1) + (2x + 2) = 1
Which statement shows a correct next step in solving the equation?
The equation can become 6x + 1 = 1 by combining like terms.
The equation can become 3x + 4x = 1 by solving the terms in the brackets.
The equation can become 3x + 4x = 1 by applying the associative property of multiplication.
The equation can become 6x + 1 = 1 by applying the distributive property.

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Looking for something else?

Not the answer you are looking for? Search for more explanations.